2023
DOI: 10.18178/ijiet.2023.13.2.1801
|View full text |Cite
|
Sign up to set email alerts
|

Technological Acceptance Model for Social Media Networking in e-Learning in Higher Educational Institutes

Abstract: Twitter and Facebook are popular among college educators. The use of social media in schools of higher learning has also been the subject of study. The use of social media has opened up new avenues of contact, collaboration, and participation between students and teachers. Accepting students and educators who make use of technological tools to do so requires insight into the factors that shape their propensity to do so. Using the Technology Acceptance Model (TAM) framework, which highlights perceived ease of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The substantial engagement in following English language learning accounts (45.8%) also suggests a preference for carefully selected language content. Additionally, interaction through comments (33.1%) and seeking advice from TikTok creators (31.4%) demonstrate the collaborative nature of language learning on TikTok, mirroring the trends seen in community exploration on social media platforms (Ajibade & Zaidi, 2023;Lee, 2023).…”
Section: Research Question 1: To What Extent Do Malaysian Undergradua...mentioning
confidence: 85%
“…The substantial engagement in following English language learning accounts (45.8%) also suggests a preference for carefully selected language content. Additionally, interaction through comments (33.1%) and seeking advice from TikTok creators (31.4%) demonstrate the collaborative nature of language learning on TikTok, mirroring the trends seen in community exploration on social media platforms (Ajibade & Zaidi, 2023;Lee, 2023).…”
Section: Research Question 1: To What Extent Do Malaysian Undergradua...mentioning
confidence: 85%
“…The WLAN framework is indispensable for online learning, while the criteria that must be met in the online learning process are Teacher Competence (TC), Student Readiness (SRD), Competitive Pressure (CPR), and Equipment readiness (DRD) this is an online learning feature using WLAN devices, and TAM variables include Perceived Usefulness (PU), Perceived Ease of Use (PEU), and Attitude Toward Using (ATU) [13][14][15][16][17][18][19][20]. From the WLAN and TAM integration model, an online learning technology (AOL) acceptance model is obtained.…”
Section: Design Of Wireless Local Area Networkmentioning
confidence: 99%
“…Furthermore, the ease and usefulness of social media for learning and teaching reflect teachers' and students' intentions. A study by (Ajibade & Zaidi, 2023) found that a greater value for perceived usefulness and perceived ease of use is indicative of a stronger inclination to adopt and use social media.…”
Section: Perceived Ease Of Use and Perceived Usefulnessmentioning
confidence: 99%